Clomiphene-induced myocardial infarction in a young male: A case report of a rare cardiovascular complication - Zubair Shahid (16441927) (2025)
Clomiphene citrate is commonly prescribed to treat male hypogonadism due to its ability to increase endogenous testosterone levels while preserving fertility. Although it is generally considered safe, and rare serious cardiovascular events have been reported. We present the case of a male in his early 30s with no known cardiovascular risk factors who developed an acute inferior-posterior ST-elevation myocardial infarction while taking clomiphene for infertility. Coronary angiography revealed complete occlusion of the distal right coronary artery due to a heavy thrombus burden, with no underlying atherosclerotic disease. The patient was successfully treated with aspiration thrombectomy and conservative medical management. This case underscores a potential, albeit rare, association between clomiphene use and myocardial infarction, warranting caution in its use—even among individuals without traditional cardiovascular risk factors. Other Information Published in: Science Progress License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/00368504251349392